Problematic Internet Use pada Remaja Akhir di Kabupaten Karawang: Mengungkap Peran Kecemasan Sosial dan Peer Attachment - Hana Nirmala; Dinda Aisha; Ananda Saadatul Maulidia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
High internet use among adolescents has the potential to increase the risk of problematic internet use, which can lead to psychological problems such as anxiety, stress, and depression, as well as barriers to social interaction, especially in late adolescents who are no longer under parental supervision. This study aims to examine how social anxiety and peer attachment influence problematic internet use among late adolescents in Karawang Regency. A quantitative approach was used with a research design focused on causality. The study population was late adolescents aged 17-21 years who use the internet in Karawang Regency, with a quota sampling technique. The number of respondents in this study was 386 people determined based on the Isaac and Michael formula with a 5% error rate. The instruments used included the Problematic Internet Use Questionnaire-Revised (PIUQ-R), the Social Anxiety Scale for Adolescents (SAS-A), and the Inventory of Parent and Peer Attachment (IPPA) peer attachment section. Data analysis was performed using SPSS 26.0 with multiple linear regression analysis techniques to examine the effect of social anxiety and peer attachment on problematic internet use. The results of the study indicate that social anxiety and peer attachment simultaneously have a significant influence on problematic internet use, with a significance value of 0.000 < 0.05. Partially, social anxiety and peer attachment also show a significant influence on problematic internet use. Furthermore, the contribution of social anxiety and peer attachment to problematic internet use is 37.2% (R Square 0.372) while the remaining 62.8% is influenced by other variables not discussed in this study.